KRITIK ATAS KRITIK MATAN JONATHAN A.C. BROWN - Kholis, Nur (TAJDID: Jurnal Ilmu Ushuluddin, 2021)
This paper examines the thesis of Jonathan A.C. Brown in his article, entitled The Rules of Matn Criticism: There Are No Rules. One of the critical issues highlighted by Jonathan A.C. Brown in this paper that deserves to be investigated is the potential for subjectivity in the practice of matn criticism. The matn criticism referred to here is more directed to the criticism of the substance of matn; that the content of a hadith must be in line with or not contradict several arguments (dalil) such as verses of the Koran, more authentic hadiths, historical facts, reason and senses or science. Up to now, scholars have not agreed on what can be used as indicators of matn criticism. The potential for subjectivity can also occur in determining the coherence of the content of a hadith with the arguments mentioned earlier (dalil). Using an analytical approach and the perspective of hadith sciences as an analytical tool, the author assesses what Jonathan A.C. Brown has discussed in his article as a scientific finding that deserves to be examined in depth. In addition, this paper provides a scientific argument as to why scholars place more emphasis on sanad criticism as the initial and primary step in the hadith validation process rather than matn criticism. The author also finds that the authoritative subjective theory proposed by Jonathan A.C. Brown to tackle the element of subjectivity is an idea that scientifically deserves to be used as a standard of reference and further discussion. Tulisan ini menelaah ulang pemikiran Jonathan A.C. Brown dalam karyanya The Rules Matn Criticism: There Are No Rules. Salah satu problem penting yang diangkat oleh Jonathan Brown dalam tulisan ini yang layak untuk dikaji adalah adanya potensi subjektifitas dalam praktek kerja kritik matan. Kritik matan yang dimaksud di sini lebih mengarah kepada kritik substansi matan bahwa kandungan sebuah hadis haruslah sejalan atau tidak bertentangan dengan sejumlah dalil seperti ayat al-Quran, hadis yang lebih sahih, fakta sejarah, akal dan indera atau ilmu pengetahuan. Para ulama hingga kini belum bersepakat atas apa saja yang dapat dijadikan indikator yang harus koheren, potensi subjektifitas tersebut juga dapat terjadi pada praktek menentukan koherensi kandungan sebuah hadis dengan dalil yang telah disebutkan tadi. Dengan menggunakan pendekatan analitis dan cara pandang ilmu hadis sebagai payung besar, penulis menilai apa yang diangkat oleh Jonathan A.C. Brown merupakan temuan ilmiah yang layak untuk dikaji secara mendalam. Selain itu pula, tulisan ini memberikan argumentasi ilmiah kenapa para ulama lebih menitik beratkan kritik sanad sebagai langkah awal dan pokok dalam proses validasi hadis dibanding kritik matan. Penulis juga menemukan teori subjektif otoritatif yang diajukan oleh Jonathan Brown untuk menanggulangi unsur subjektifitas merupakan sebuah gagasan yang secara ilmiah layak untuk dijadikan bahan acuan dan penelitian lebih lanjut.